THE APPLICATION OF PLASTIC FIBER OPTIC SENSOR AS BLOOD PRESSURE MONITORING - Ama, Fadli; Hatta, Agus Muhamad; Indriawati, Katherin; Agustiyanto, Frans R; Usamah, Shofi Afghania; Putra, Alfian Pramudita; Perkasa, Sigit Dani (Indonesian Physical Review, 2025)
Continuous blood pressure monitoring is essential for early hypertension prevention and cardiovascular disease diagnosis. Traditional methods are unsuitable for long-term use due to discomfort and limited portability. This study presents a tapered plastic fiber optical sensor (PFOS) as a sustainable, non-invasive solution for continuous monitoring. The PFOS system employs a light modulator based on mechanical waves to detect arterial pressure changes, utilizing an infrared light source (940 nm). The cuffless design includes four configurations: Bend, Bend with 1 Scratch, Bend with 3 Scratches, and Straight with 3 Scratches. The Bend with 1 Scratch configuration demonstrated superior performance, achieving 99.84% accuracy, a mean absolute error (MAE) of 0.1564, a linearity of 0.9999, and a sensitivity of 2.9997 Hz/dBm. Experimental validation involved testing radial and brachial arteries. Blood pressure estimates from Pulse Transit Time (PTT) were compared to a standard sphygmomanometer. On the radial artery, the Bend with 1 Scratch configuration achieved the best results, with the lowest MAE (1.72 for SBP, 2.39 for DBP) and highest accuracy (98.30% for SBP, 96.56% for DBP). The Straight with 3 Scratches configuration performed best on the brachial artery, with an MAE of 2.81 for SBP and 5.11 for DBP, and accuracies of 97.21% for SBP and 92.67% for DBP. The PFOS system offers a promising option for continuous monitoring in clinical and home settings. Â